The double burden of food and water insecurity: Implications for health, equality, and policy - Chakrabarti, Suman (JAMA, 2025)
Food and water insecurity reflect a lack of reliable access to sufficient, safe, and affordable food and water to meet basic human needs. Both have significant impacts on nutrition, physical and mental health, learning, and family cohesion; however, their combined effects remain understudied. With a high co-occurrence observed across numerous low- and middle-income countries (LMICs), these insecurities are rooted in systemic factors, such as poverty, climate-related environmental stressors, resource scarcity, inadequate public infrastructure, weak governance, and conflict. Wang et al examined the association of the co-occurrence of food and water insecurity with functional disabilities in Ecuadorian adults. This novel research builds on emerging evidence on the intersectional implications of food and water insecurity for human well-being.